Triple therapy combinations for the treatment of type 2 diabetes - A network meta-analysis - Lee, Crystal; Woodward, M.; Colagiuri, S. (Elsevier Ireland Ltd, 2016)
Aim: To estimate and compare the results from all randomised trials of triple combinations of anti-diabetes therapies that reported the reduction of glycated haemoglobin (HbA1c) and associated effects on body weight and hypoglycaemia. Methods: PubMed and the Cochrane Library were searched for trials with at least one study arm on triple therapy and which reported the differences in mean change in HbA1c between two study arms. These were included in a network meta-analysis. Results: Altogether, 15,182 participants from 40 trials with treatment duration of 6-12 months were included. Compared with none/placebo added to dual therapy, the addition of a drug therapy from six of eight drug classes to existing dual therapy resulted in significant additional mean reductions in HbA1c from -0.56% (-6.2 mmol/mol; dipeptidyl peptidase 4 inhibitors) to -0.94% (-10.3 mmol/mol; thiazolidinediones). Of the six drug classes, three were associated with less favourable weight change and two were associated with more favourable weight change when compared with none/placebo added to dual therapy. Furthermore, five drug classes were associated with greater odds of hypoglycaemia. Similar results were observed in analyses of studies with a 6 month treatment duration and after excluding study arms that contained insulin. Conclusions: Overall triple therapy combinations were similar in improving diabetes control although there were some differences in adverse effects. By balancing the risks and benefits of each therapy, the estimates of pairwise comparisons of triple therapies for HbA1c, body weight and hypoglycaemia provided in this study may further inform evidence based practice.